Prasa we Lwowie w latach 1914-1939.Typologia i statystyka = The Press in Lviv from 1914 to 1939. Typology and Statistics - Jarowiecki, Jerzy (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The aim of this article is to provide a quantitative analysis and typology of the press published in Lviv during World War I (1914-1918) and the interwar period (1918-1939), based on extensive bibliographic and library research. The outbreak of World War I negatively impacted the dynamically developing Polish press in the city on the Poltva River during the autonomous period of Galicia. In the first post-war years, the Lviv press faced significant challenges, not only financial. Nevertheless, the growth of culture and science ? which, even under foreign rule, thrived as a form of national self-defense during the partition period ? positively influenced its development. After Poland regained independence, the literary community expanded, often in connection with emerging journals. Lviv became one of the four largest publishing centres in the country, and its press was second in stability only to that of Greater Poland. In addition to Polish titles, numerous Ukrainian-language periodicals and Jewish minority publications were also in circulation. This study is richly documented with tables and graphs that provide numerical data on newly founded and discontinued publications from 1918 to 1939, illustrating the frequency and typology of the Lviv press as well as its resilience in a city enriched by its diversity of ethnic communities.
Keywords: Lwów w latach 1914-1939; początki niepodległości Polski we Lwowie; walka polsko-ukraińska o Lwów 1918-1919; polska prasa we Lwowie 1914-1939; Lviv in 1914-1939; beginnings of Polish independence in Lviv; Polish press in Lviv 1914-1939; Polish-Ukrainian struggle for Lviv 1918-1919